2022
DOI: 10.3389/fendo.2022.935759
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide-Induced Shrinkage in GH and ACTH Secreting Pituitary Adenoma: A Systematic Review and Meta-Analysis

Abstract: IntroductionPasireotide (PAS) is a novel somatostatin receptor ligands (SRL), used in controlling hormonal hypersecretion in both acromegaly and Cushing’s Disease (CD). In previous studies and meta-analysis, first-generation SRLs were reported to be able to induce significant tumor shrinkage only in somatotroph adenomas. This systematic review and meta-analysis aim to summarize the effect of PAS on the shrinkage of the pituitary adenomas in patients with acromegaly or CD.Materials and methodsWe searched the Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…One the other hand, active disease under first-generation SSAs represents an indicator of a more severe form, most patients becoming candidates for either pasireotide or pegvisomant in terms of pharmacological intervention [ 20 , 66 , 67 ]. Other comorbidities with a major impact on overall health are represented by cardio-metabolic complications, particularly HBP and DM, which are partially controlled by standard intervention for acromegaly [ 68 , 69 , 70 ].…”
Section: Cardio-metabolic Features In Pregnant Females With Acromegalymentioning
confidence: 99%
“…One the other hand, active disease under first-generation SSAs represents an indicator of a more severe form, most patients becoming candidates for either pasireotide or pegvisomant in terms of pharmacological intervention [ 20 , 66 , 67 ]. Other comorbidities with a major impact on overall health are represented by cardio-metabolic complications, particularly HBP and DM, which are partially controlled by standard intervention for acromegaly [ 68 , 69 , 70 ].…”
Section: Cardio-metabolic Features In Pregnant Females With Acromegalymentioning
confidence: 99%
“…These results are in line with those previously published. 27 Another relevant aspect of the imaging analysis of the tumour in patients with acromegaly treated with pasireotide is the dynamic changes observed over time, as described by Coopmans et al 21 In this later study, sequential imaging while on pasireotide treatment showed that a number of cases presented an increment in the hyperintense signal and this increase correlated with the magnitude of shrinkage effect as well as the hormonal control. The interpretation was that a cytolytic effect would apply in those patients, leading to a tumour mass reduction and in parallel to an amelioration of hormonal hypersecretion, probably also related to a decrease in viable somatotroph cellular mass.…”
Section: Discussionmentioning
confidence: 64%
“…IGF-1 concentrations significantly decreased during the study and normalized in 58% of the included patients. Furthermore, the positive effects on tumor size ( 12 , 39 ) could be confirmed, as an increase of more than 20% in tumor size was observed only in a single patient.…”
Section: Discussionmentioning
confidence: 81%